ACCOUNTING EDUCATION BASED ETHICS: CHALLENGES AND OPPORTUNITIES - Fadjar OP Siahaan (Universitas Trunojoyo Madura, 2012)
Professional accountants are the person who play very important role in every industrial organization. Investors and other decision makers rely heavily on professional accountants related to the use of financial accounting and reporting, effective financial management and competent advice on a variety of business and taxation matters. Since the accuracy of decisions depends on the reliability of accounting information, the ethical dimension of the profession has gained considerable attention. The recent of accounting scandals such as Enron and World Com, have defame the reputation of accounting professions. This incident brought attention to the importance of accounting ethics education.